Shaping health policy case study methods and analysis - Exworthy, Mark 1966-; Peckham, Stephen; Powell, Martin; Hann, Alison (Policy Press, 2012)
This collection examines the role that studies play in understanding and explaining British health policy. Overall, the chapters cover key health policy literatures in terms of the policy process, analytical frameworks and some of the seminal moments of the NHS. They have been written by leading health policy researchers in sociology, social policy, management and organisation studies. The collection explores and promotes the case study as an under-used method and thereby encourages a more reflective to policy learning by practitioners and academics.